Evaluate of Chill Vent Performance for High Pressure Die-Casting Production and Simulation of Motorcycle Fuel Caps - Piyanut Meethum (2018)
© The Authors, published by EDP Sciences, 2017. Inappropriate air vent design always induced porosities in thin and complex shape of high pressure die-casting (HPDC) products. Chill block installation was preferred to improve permanent molds for reducing porosities. There were not regular to obtain an appropriated chill vent from this method unless an experience of mold makers. This research was performed to investigate and evaluate the chill block performance in the HPDC mold of motorcycle fuel caps. The HPDC mold of the thin and complex shape product without chill vents was improved by inserting of chill blocks. The motorcycle fuel caps of molds with and without chill vents were compared to verify size and position of porosity defects. Furthermore the HPDC simulation using the finite element analysis (FEA) had been performed according to the physical experiment. The FEA results were compared and in agreement with the experimental data. Therefore an improvement of the HPDC mold should be used FEA to obtain the best way of the air vent design.